WORK-LIFE BALANCE AND MODERN ORGANIZATIONAL BEHAVIOR: A SYSTEMATIC REVIEW OF THE CHALLENGES OF REMOTE WORK AND BURNOUT - Suryowanto; Andaryanto; Sopiah (RADJA PUBLIKA, 2025)
The transformation of the global work landscape driven by digitalization and the pandemic has rapidly accelerated the widespread adoption of remote work, creating an urgent need to understand the relationship between work-life balance (WLB), burnout, and the dynamics of modern organizational behavior. This study aims to synthesize scientific findings from the past five years on the interconnection of these three concepts through a Systematic Literature Review (SLR) approach guided by the PRISMA protocol. A total of 79 verified primary articles were analyzed using thematic and content analysis methods to map key trends, theoretical-methodological approaches, and relevant research gaps. The results indicate that WLB functions as a protective factor against burnout, whereas remote work exhibits ambivalent effects that depend on organizational design and behavior. This review highlights the dominance of the JD-R theory and the limitations of longitudinal studies. The main contribution of this research lies in its thematic integration of cross-cutting variables and the proposal of a synthetic model based on dynamic interaction. The study recommends the development of digital organizational behavior theory and work policies that prioritize well-being. Future research is encouraged to adopt cross-disciplinary and contextual approaches to build a more adaptive and human-centered framework.